Efektivitas Model Pembelajaran Kooperatif dalam Meningkatkan Retensi Belajar Siswa di SD Negeri Pandan Pamekasan - Sofia Ningsih; Balqis Raisa Labibah; Emna Laisa; Cyntia Ela Maghfira; Rofiq Hidayatullah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The decline in students' conceptual memory demands pedagogical innovations that go beyond conventional memorization, making cooperative learning a potential strategy to strengthen learning retention. This article aims to analyze the effectiveness of the cooperative learning model in improving students' learning retention at SD Negeri Pandan and to identify the underlying cognitive-social mechanisms. The study uses a descriptive qualitative approach with participatory observation, semi-structured interviews, and documentation studies, which are analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the effectiveness of cooperation depends on the consistent implementation of positive interdependence, individual accountability, and group processing. The mechanism of elaboration among peers, negotiation of meaning, and spontaneous social scaffolding acts as a reinforcer of long-term memory traces, resulting in better learning retention tendencies compared to conventional learning. These results contribute to the enrichment of social constructivist theory by mapping contextual variables that moderate the relationship between cooperative structures and memory consolidation in elementary schools, while also implying the need for a transformation of the teacher's role into a collaborative facilitator and evidence-based pedagogical mentor.